Electrical cardiometry significance in postoperative cardiac ICU; a single center study - Mohamed Samir; Fatma Alzahraa Mostafa; Rodina Sobhy; Amal El-Sisi; Amira El Tantawy; Hesham Mohammed Sakr; Ahmed Afifi (SpringerOpen, 2024)
Abstract Background Hemodynamic monitoring is a cornerstone of critical care; in fact, the techniques available for this purpose are either unreliable or operator-dependent or intermittent (echocardiography) and invasive (thermodilution). Objectives: To evaluate the effectiveness of electrical cardiometry (EC) in assessing hemodynamics in pediatric postoperative cardiac intensive care unit (ICU) and the agreement between EC and trans-thoracic echocardiography (TTE) as bedside tools for hemodynamic monitoring and early diagnosis of cardiovascular compromise. We included 70 pediatric patients from the postoperative cardiac ICU. All participants underwent history-taking and clinical examination. emphasising vital signs, manifestations or signs of hemodynamic instability, calculation of RACH score and vasoactive inotropic score. EC was applied for all patients, and TTE. Results The study included 40 males and 30 females with a mean age of 2.6 ± 3.49 years, ranging between 2 weeks and 13 years, with a male to female ratio of 1.3:1. The median of EC parameters were comparable to TTE parameters stroke volume (SV) (9 vs. 8 p = 0.2), stroke index (SI) (23.5 vs. 22 p = 0.2), cardiac output (CO) (1.25 vs. 1.1 p = 0.3), and cardiac index (CI) (3.2 vs. 3.15 p = 0.2). Hemodynamic parameters correlated significantly between EC and echocardiography, with significantly observed agreement between them. Four equations were postulated successfully based on a linear regression model to predict echocardiographic hemodynamic parameters in comparable groups of children, i.e., SV, SI, CO, and CI. Conclusion EC is an excellent alternative to echocardiography in hemodynamic assessment of cardiac patients in the postoperative ICU.